2010
DOI: 10.1088/0953-8984/22/49/495301
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order nonlinear electromechanical effects in wurtzite GaN/AlN quantum dots

Abstract: As we demonstrated earlier, conventional mathematical models based on linear approximations may be inadequate in the analysis of properties of low-dimensional nanostructures and band structure calculations. In this work, a general three-dimensional axisymmetric coupled electromechanical model accounting for lattice mismatch, spontaneous polarization and higher-order nonlinear electrostriction effects has been applied to analyze properties of GaN/AlN quantum dots coupled with wetting layer. The generalized mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We may underline that in this field, incomplete formula for the M lmi tensor have been used up to now. 6,34,35 An extended and self-contained thermodynamical model of third-order electro-elastic coupling is used with symmetry analyses and DFT calculations to evaluate properly the various linear and non-linear coefficients. It is shown that in noncentrosymmetric materials, electrostrictive and non-linear piezoelectric phenomena are strongly coupled, except for materials crystallizing in a cubic lattice associated to point group 432.…”
Section: -3mentioning
confidence: 99%
“…We may underline that in this field, incomplete formula for the M lmi tensor have been used up to now. 6,34,35 An extended and self-contained thermodynamical model of third-order electro-elastic coupling is used with symmetry analyses and DFT calculations to evaluate properly the various linear and non-linear coefficients. It is shown that in noncentrosymmetric materials, electrostrictive and non-linear piezoelectric phenomena are strongly coupled, except for materials crystallizing in a cubic lattice associated to point group 432.…”
Section: -3mentioning
confidence: 99%
“…However, there are serious indications that deviations from this simple rule should be expected in the a) Electronic mail: m.lopuszynski@icm.edu.pl case of elastic properties, 4-7 similarly to, e.g., nonlinear dependence on composition predicted for piezoelectric properties 8 . Since subtle nonlinear effects in elasticity and electrostriction proved to be significant when modeling nitride devices, [9][10][11] also the accurate composition dependence of c ij can be of interest, for correct and accurate description of nanostructures. In the present study, we give a detailed overview of influence of composition on c ij in random wurtzite Al x Ga y In 1−x−y N. The work is based on our previous calculations for cubic phases.…”
Section: Introductionmentioning
confidence: 99%
“…As it shown in [31] such influence can be quite important in a number of practically situations. The authors of [31] were the first to use a general three-dimensional axisymmetric coupled electromechanical model accounting for lattice mismatch, spontaneous polarization and higher-order nonlinear electrostriction effects in the application to the analysis of properties of quantum dots coupled with wetting layer. Notwithstanding that their generalized model that accounted for five independent electrostriction coefficients was efficiently solved numerically via a finite-element-method (FEM) implementation.…”
Section: Mathematical Model For Coupling Classical and Quantum Mementioning
confidence: 92%
“…Notwithstanding that their generalized model that accounted for five independent electrostriction coefficients was efficiently solved numerically via a finite-element-method (FEM) implementation. The model (1)- (13) implemented here also via the FEM strategy can be extended to account for higher order nonlinear electromechanical effects in a way similar to [31]. Such effects are known to influence optoelectronic properties in bandstructure calculations based on a multiband effective mass theory.…”
Section: Mathematical Model For Coupling Classical and Quantum Mementioning
confidence: 99%